Pengaruh Budaya Organisasi Terhadap Produktivitas Kerja Karyawan PT. Japfa Comfeed, Tbk. Unit Makassar - Indira Aprilia; Azhary Ismail; Monalisa Monalisa (Jurnal Pengembangan Ketenagakerjaan, 2023)
This research is Organisational Culture on employee performance at PT. Japfa Comfeed Tbk Makassar Unit. The data used in this study is primary data, the sample used was 150 employees. The data analysis method uses simple linear analysis techniques. The data collection technique used is by using a research instrument is a questionnaire. The data analysis technique is by using SPSS 23.0 software. The results of this study prove that organisational culture affects the productivity of employees.